A poética da esperança: sentidos políticos nas memórias de Nelson Mandela - Silva, Cristiane Mare da (2016)
The present study was developed at the Postgraduate Program in History, of the Pontifical Catholic University of São Paulo and has as object biographical and autobiographical texts of the South African Nelson Mandela, that allows us to seize moments and statements, guiders of the struggle for equality, the exercise of tolerance and human rights, not only in South Africa, but everywhere where there are conflicts inside a population, especially in the Western Hemisphere. Interests me, particularly, identify strategies and discursive paths built in biographical narratives in the representations of Nelson Mandela, the works presented will be, Mandela Struggle is my life, organized by the The International Defence and Aid Fund of 1989, first published in 1978 in English. Mandela: The Authorized Portrait 2007. Mandela's Way: Lessons on Life, Love, and Courage, of 2010, whose author is Richard Stengel. Mandela: Conversations With Myself, of 2010, Nelson Mandela Foundation. Mandela: Long Walk to Freedom (2012) (autobiography), seeking how Mandela is seized in these pages. Through the reading of authors such as Frantz Fanon, Achille Mbembe, Hampaté Ba, Anibal Quijano, Jeanne Marie Gagnebin and Sabina Loriga, I sought to understand how Madiba, through a rereading of his traditions, invented a policy making which made possible the transition from the Apartheid Regime to democracy in South Africa. The problem that I developed as structuring to the work: what Africa has to teach us in the production of decolonial policy pathways, especially the experience of South African leader Nelson Mandela in his government practice